Professional self-awareness of language teachers – how to equip pre-service students? - Sujecka-Zając, Jolanta; Szymankiewicz, Krystyna (Glottodidactica, 2022)
The aim of the text is to discuss the possibilities of developing professional self-awareness at the stage of initial education of foreign language teachers. The first part of the article presents theoretical considerations on teachers’ professional self-consciousness, distinguishing three areas of it: professional competence as goals to be achieved, self-evaluation and self-regulation, and teachers’ cognitive, emotional and communicative functioning in professional situations. The second part of the text contains an analysis of selected practical tools that serve to develop teachers’ professional self-awareness, such as The European Portfolio for Student Teachers of Languages, and the European Profiling Grid, tools inspired by E. Berne’s concept of Transactional Analysis, and the author’s reflection grids. The conclusions of the analysis indicate the possibility of the coherent use of available tools and creation of additional tools within the context of education, so that the process of developing teachers’ self-awareness is multifaceted and leads to a sense of professionalism.